2006
DOI: 10.1111/j.1540-8191.2006.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical Cooling for Myocardial Protection: The Results of a Prospective Randomized Study of the "Shallow Technique"

Abstract: ST likely reduces the incidence of postoperative PNI and might be protective mainly in the event of ITA harvest. It should be considered as a valuable tool for myocardial protection protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
2
0
3
Order By: Relevance
“…Similarly, Cassese et al found that phrenic nerve injury and failure of extubation occurred more frequently with the use of iced slush (P = 0.009 and P = 0.034, respectively). 12 Additionally, Maccherini et al in their study titled "Warm heart surgery eliminates diaphragmatic paralysis", found that topical hypothermia causes transitory diaphragmatic paralysis, pleural effusions, and thoracentesis. 13 The opponents of Topical cooling with iceslush suggested that such maneuver does not provide additional cardioprotective effects, and is an unnecessary adjunct to myocardial protection in patients undergoing cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Cassese et al found that phrenic nerve injury and failure of extubation occurred more frequently with the use of iced slush (P = 0.009 and P = 0.034, respectively). 12 Additionally, Maccherini et al in their study titled "Warm heart surgery eliminates diaphragmatic paralysis", found that topical hypothermia causes transitory diaphragmatic paralysis, pleural effusions, and thoracentesis. 13 The opponents of Topical cooling with iceslush suggested that such maneuver does not provide additional cardioprotective effects, and is an unnecessary adjunct to myocardial protection in patients undergoing cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Necessity for drainage and amounts of pleural effusions, diaphragm paralysis and elevations were recorded. Diaphragm changes above two or more ribs were determined as a positive result, according to the current literature data 3. Positive echocardiographic changes were determined as follows: new development of valve disorders, structural or transactional changes of the ventricular wall, aneurysm formation and a decrease in EF of more than 10%.…”
Section: Methodsmentioning
confidence: 99%
“…Die myokardiale Hypothermie hat heute also nur einen geringen Anteil an der Protektion; in klinischen Untersuchungen hat auch eine topische Kühlung keine zusätzlichen Vorteile gezeigt [4]. Sie kann als Komplikation aber zu kältebedingten Phrenikusschä-den führen [8]. Nur bei langen Ischämie-zeiten oder besonderen Risikopatienten könnte eine zusätzliche Kühlung mit einer kalten gegenüber einer warmen Kardioplegie Vorteile bringen [22,26].…”
Section: Hypothermie Und Myokardprotektionunclassified
“…Reduzierung der operativ notwendigen Ischämie entwickelt und mit sehr guten Ergebnissen eingesetzt. Neben einer guten Metaanalyse zur Kardioplegie von Guru et al [11] kann hier aus der Vielzahl der Arbeiten zu diesem Thema nur auf einige aktuelle hingewiesen werden [8,22,26]. Zusammenfassend ist festzustellen, dass eine zusätzliche topische Küh-lung und die Verwendung kalter, kristalloider Kardioplegielösungen zunehmend verlassen werden, da eine systemische Normothermie und eine Myokardprotektion mit einer Blutkardioplegie günstige-re Ergebnisse zeigen und dabei die Nachteile einer Hypothermie vermieden werden.…”
Section: Hypothermie Und Myokardprotektionunclassified